High pressure phonon and thermodynamic properties of Ru based intermetallics: A DFT investigation. (November 2018) - Jain, Ekta; Pagare, Gitanjali; Dubey, Shubha; Sharma, Ramesh; Sharma, Yamini
Abstract: First-principles calculations have been carried out to investigate the structural, electronic, phonon and thermodynamic properties of RuX (X = Sc and Ti) intermetallic compounds within the framework of density functional theory. The ground state properties such as lattice parameter (a0 ), bulk modulus (B) and pressure derivative of bulk modulus (B′) have been determined and found in accordance to the available experimental and theoretical results. The electronic investigation presents metallic character for these compounds. The electron localization function confirms the dominant ionic bonding between Ru and X. The ductility of these compounds is predicted due to zero frequency gap between optic and acoustic branches of phonon dispersion curves. The phonon dispersions and phonon density of states indicate the stability of these compounds in B2 -type (CsCl) crystal structure at 0 GPa and 20 GPa. Further we have for the first time, predicted the variation of various thermodynamic parameters including Debye temperature, Grüneisen parameter and thermal expansion for these compounds in the temperature range of (0–2000 K) at different values of pressure (0–100 GPa). Graphical abstract: Image 1 Highlights: The negative values of the formation energy and the positive value of frequency confirms the stability in B2 -phase. The electron localization function confirms the dominant ionic bonding between Ru and X. The density of states at higher frequency are mainly composed of 'X' states due to their lighter mass than Ru. The calculated and experimental melting temperature shows good agreement.